Des pratiques réflexives de groupe en contexte de recherché sociale et de formation personnelle - Bourassa, Bruno; Leclerc, Chantal (Canadian Journal of Counselling and Psychotherapy, 2007)
One of the most important assumptions of traditional science is that knowledge precedes action. Some theories criticize this assumption and, in contrast, recognize the heuristic potential of action for knowledge. Practitioners such as those working in guidance and counselling may be considered as the producers of knowledge. However, this experiential knowledge, built on a daily basis to meet the needs of clients confronted by ever-changing social and professional contexts, often remains tacit. In this article, different reflective practices intended to uncover this experiential knowledge are discussed. As well, the theoretical background of these practices and their applications in research and continuing education are addressed.